New records of fruit flies (Diptera: Tephritidae) in the Alagoas State, Brazil - Silva Da Costa, Simone; Dos Santos, Jakeline Maria; Forti Broglio, Sônia Maria; Dias-Pini, Nivia Da Silva; Gómez-Torres, Mariuxi (Revista Colombiana de Entomología, 2019)
The aim of this study was to determine the diversity of fruit flies, their hosts and parasitoids in the State of Alagoas, Brazil. A total of 17,394 specimens of frugivore insects where recorded, of which 14,993 (86.2 %) belonged to the genus Anastrepha (7,224 females and 7,769 males) and 2,401 (13.8 %) belonged to Ceratitis (1,196 females and 1,205 males). In Maceió, a new species of Anastrepha, which so far has been referred to as “morpho-species of Anastrepha sp.”, has been collected. Besides showing the highest number of females collected during this study, Anastrepha obliqua was associated with the highest number of host species (eight species). Parasitoid emergence was associated with only 9 of the 19 fruit species infested with fruit flies. From all pupae of Anastrepha obtained in this study (26,724), 6,125 parasitoid specimens have emerged, with 5,870 corresponding to Braconidae, 169 to Pteromalidae, 78 to Figitidae and 8 to Torymidae. In this study the emergence of parasitoids from puparia of Ceratitis was not recorded.